PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT BANK PERKREDITAN RAKYAT PRISMA DANA MANADO - Febbisania F Lalawi; Selfy Manueke; Precylia R Rambing; Iyam L. Dua (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2023)
PT Bank Perkreditan Rakyat (BPR) Prisma Dana Manado is a company engaged in the banking sector. This company experiences various problems of employees who have excessive tasks while the compensation received is not in accordance with the number of tasks carried out. This study aims to determine the effect of compensation on employee performance at PT BPR Prisma Dana Manado. The research method used is a quantitative method with 2 variables, namely variable X is compensation and variable Y is employee performance. The analytical method used is the method of correlation and simple regression. The research results obtained indicate that there is a correlation between compensation and employee performance where compensation has a very strong relationship (r = 0.821) with employee performance, which means that if compensation increases, employee performance also increases. Likewise, the results of the simple regression analysis (Y=-3.575+ 1.162) show that compensation has a significant effect on employee performance. As a recommendation, the company should pay more attention to compensation for each employee based on the work of each employee so that employees can be satisfied and make their performance increase. In addition, the company must pay more attention to giving fair rewards to all employees such as bonuses, leave pay, and other incentives.